Bulgarian Human Trafficking in Belgium and Proactive Learning Entrepreneurship: Developments 2002–2009 - Johan Leman; Stef Janssens (Migracijske i etničke teme, 2010)
The paper discusses the mechanisms of proactive learning in the Bulgaro-Belgian human trafficking business between 2002 and 2007 through three profiles, starting each time with a case study. The profiles and cases are the result of an in-depth study of 16 Belgian court files. The study reveals three profiles: post-violent entrepreneurship in prostitution (2002–2005), international and inter-ethnic entrepreneurship in prostitution (2004), and labour exploitation (2004–2005). Each time one can identify learning processes in the minds of the entrepreneurs when comparing their activities with those of their predecessors, as described in previous articles by the same researchers. The image that comes to the fore from our analysis is one of organisations that are successful in all sorts of ways at covering themselves against police and judicial investigations, and that at the same time in many places and many ways – both in the regions of origin and in the country in which the activities take place – manage to infiltrate the economy.